Salesforce essentials for administrators : discover the administration fundamentals and challenges of Salesforce CRM - Shrivastava, Mohith (Professional expertise distilled., 2014)
This book is targeted at expert administrators or professionals who are new to Salesforce and want to learn the various features supported by the platform in a short space of time. The book can also be used by professionals preparing for Developer and Administrator certification exams from Salesforce.